The role of trust on investors' intention to shares waqf in Indonesia - Amin, Irsyad Ali; Al Arif, M. Nur Rianto (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study examines the direct and indirect relationships between the variables of waqf literacy, reputation, and integrity and investors' intentions in waqf shares.Methodology – This study uses the Smart Equation Modeling (SEM) analysis approach with SEM PLS 4.0. A total of 247 investors were obtained through the questionnaire distribution.Findings – The results of this study indicate that waqf literacy, reputation, and integrity have a significant positive direct effect on trust and investor intention in waqf shares. The trust variable has a significantly positive effect on investor intention in waqf shares. The trust variable can moderate the influence of waqf literacy, reputation, and integrity on investor intention in waqf shares.Implications – For future researchers to enrich research on share waqf by adding other factors, discussing case studies specifically on share waqf nazirs, and comparing their management with other countries. To establish cooperation with stock exchange members who have Sharia Online Trading System (SOTS) services to make it easier for investors to share waqf. Originality – This study adds trust variables as mediation for other variables and revalidates the results of the influence of waqf literacy, reputation, and integrity on investor intention in waqf shares.